Potent inhibition of Severe Acute Respiratory Syndrome Coronavirus 2 by photosensitizers compounds. (October 2021) - Yu, Shujuan; Sun, Gaohui; Sui, Yaqun; Li, Hanlin; Mai, Yuhan; Wang, Guodong; Zhang, Ning; Bi, Yuhai; Gao, George F.; Xu, Peng; Jiang, Longguang; Yuan, Cai; et al.
Abstract: The ongoing pandemic of coronavirus disease 2019 (COVID-19) posed a major challenge to the public health. Currently, no proven antiviral treatment for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection is available. Here we report compounds pentalysine β-carbonylphthalocyanine zinc (ZnPc5K) and chlorin e6 (ce6) potently inhibited the viral infection and replication in vitro with EC50 values at nanomolar level. These compounds were first identified by screening a panel of photosensitizers for photodynamic viral inactivation. Such viral inactivation strategy is implementable, and has unique advantages, including resistance to virus mutations, affordability compared to the monoclonal antibodies, and lack of long-term toxicity.